Advancing sustainable healthcare through multidisciplinary stroke team rehabilitation - Persson, Hanna C.; Reinholdsson, Malin; Lange, Elvira; Barna, Stefi; Palstam, Annie (Frontiers in Stroke, 2025)
Empirical studies evaluating stroke team rehabilitation interventions from a sustainability perspective are scarce. This paper highlights the significant role of multidisciplinary stroke team rehabilitation in promoting sustainable healthcare by applying principles of sustainable healthcare. Climate change and air pollution are significant risk factors for stroke and other cardiovascular diseases. Healthcare contributes to 5% of global CO2 emissions, exacerbating the disease burden associated with climate change. The vulnerability of individuals with disabilities to climate change has been highlighted, calling for global collaboration to address climate justice and health equity. This paper argues that multidisciplinary stroke team rehabilitation is essential for achieving sustainable stroke care, optimizing patient functioning, and contributing to all principles of sustainable healthcare: prevention, patient empowerment, lean pathways, low carbon alternatives, and efficient resource use. Timely assessments and dose-specific interventions are crucial for successful outcomes, providing significant co-benefits for healthcare resource use. Enhancing self-management and patient empowerment reduces healthcare utilization without compromising health outcomes. Telerehabilitation increases accessibility to healthcare services, particularly where transportation is challenging, and complements hospital-based procedures. Preventive healthcare activities, with their low carbon footprint, offer strong incentives for optimizing secondary prevention in stroke. Overall, multidisciplinary stroke team rehabilitation aligns with all sustainable healthcare principles, reducing overall healthcare consumption through optimized functioning and health. Increased investment in rehabilitation resources leads to better quality of care and reduced long-term resource use. By integrating sustainable practices, stroke team rehabilitation can significantly contribute to sustainable healthcare, addressing both human and planetary health.